Effect of sinusoidal geometry on shear capacity of profiled web girder using finite element method - Zulhelmi Bin Zulkeflee (School of Environmental Engineering, University Malaysia Perlis, 2014)
Main objective of this research is to study behaviour of sinusoidal plate girder, effect of the web thickness, effect of the web geometry dimension on shear capacity and compare sinusoidal profiled web capacity with conventional flat girder. Modelling is using sine function as profiled geometry of the web and thin shell element of meshing. Material strain hardening parameter limited only elastic-perfect plastic model. Linear analysis has been done to predict the buckling mode and geometry imperfection.